Establishment of tissue culture protocol of two Bangladeshi sunflower varieties (Helianthus annuus L.) - Obaid, Nadia Binte (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2018.